2018
DOI: 10.1515/nanoph-2018-0093
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in terahertz difference-frequency quantum cascade laser sources

Abstract: Terahertz quantum cascade laser (QCL) sources based on intra-cavity difference frequency generation are currently the only electrically pumped monolithic semiconductor light sources operating at room temperature in the 1–6-THz spectral range. Relying on the active regions with the giant second-order nonlinear susceptibility and the Cherenkov phase-matching scheme, these devices demonstrated drastic improvements in performance in the past several years and can now produce narrow-linewidth single-mode terahertz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 80 publications
0
52
0
Order By: Relevance
“…The operating range of QCL combs was extended to the THz range too [15,[20][21][22][23][24], where, owing to the intrinsic broadband nature of the waveguides, octave spanning emission has been reported [25] with the relative bandwidth coverage in comb operation as high as Df/f= 36% [26]. It has to be noted that operation of THz QCLs is for the moment limited to cryogenic temperatures, even though promising results are coming from on-chip THz DFG with Mid-IR devices [27]. Moreover, experiments have shown that these devices are well adapted for spectroscopy, as their linewidth is Schawlow-Townes limited for short time scales [28], the equidistance between the modes is demonstrated to be better than 1 part per 10 13 [51], and they do not present excess amplitude noise.…”
Section: Figure1 (A)mentioning
confidence: 99%
“…The operating range of QCL combs was extended to the THz range too [15,[20][21][22][23][24], where, owing to the intrinsic broadband nature of the waveguides, octave spanning emission has been reported [25] with the relative bandwidth coverage in comb operation as high as Df/f= 36% [26]. It has to be noted that operation of THz QCLs is for the moment limited to cryogenic temperatures, even though promising results are coming from on-chip THz DFG with Mid-IR devices [27]. Moreover, experiments have shown that these devices are well adapted for spectroscopy, as their linewidth is Schawlow-Townes limited for short time scales [28], the equidistance between the modes is demonstrated to be better than 1 part per 10 13 [51], and they do not present excess amplitude noise.…”
Section: Figure1 (A)mentioning
confidence: 99%
“…The second huge limitation of THz QCLs is the need of cryogenic cooling, ultimately hindering the miniaturization of QCL-based setups, which can now be overcome with an alternative approach based on difference frequency generation (DFG) in mid-infrared QCLs [37], referred as THz DFG-QCLs [38][39][40]. Mid-infrared QCLs are engineered to provide mid-infrared gain for pumps and to possess giant second-order nonlinearity χ (2) for THz DFG in the QCL active region [38][39][40][41]. Since nonlinear processes, such as DFG, do not require any population inversion, THz DFG-QCLs are able to operate at room temperature, similar to other mid-infrared QCLs.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been recently migrated to DFG QCL devices operating in multimode regime, in which broadband THz emission is generated via nonlinear mixing between a single mid-IR pump frequency selected by a largely detuned distributed feedback (DFB) grating, and FP modes of the second mid-IR pump selected by the laser cavity [48]. The potential operation of THz combs has been assessed for multimode THz DFG-QCL devices, initially at 78 K [40], and subsequently at room temperature [49]. However, these were evaluated against the spectral coherence of mid-IR emission spectra, and by retrieval of a single and narrow intermodal beatnote (IBN).…”
Section: Introductionmentioning
confidence: 99%
“…The active region consists of two stacks of stages: In the first one, a double phonon resonance design is in action 20 and lasing takes place around a wavelength λ 1 ≈10.5μm while in the second a bound-to-continuum design is used 20 , where n g and n sub are respectively the group velocity index of the mid-IR pumps and the THz refractive index of the substrate. For more technical details on the structure, we kindly refer the reader to the published literature 18,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…efficiencies play an important role that partly determine the device's performance and have already been investigated experimentally in the case of a Čerenkov THz DFG-QC laser [23][24] . At room temperature, the maximum mid-IR-to-THz conversion efficiencies exceed 0.8mW/W 2 and 0.35mW/W 2 for pulsed 24 and CW operations 22 respectively, while the best wall-plug efficiencies of mid-IR QC lasers exceed 0.7×10 −3 % and 0.8×10 −4 % for pulsed 17 and CW operations 22 respectively.…”
Section: Introductionmentioning
confidence: 99%